Non-malignant consequences of decreasing asbestos exposure in the Brazil chrysotile mines and mills. Issue 6 (18th May 2005) - Bagatin, E; Neder, J A; Nery, L E; Terra-Filho, M; Kavakama, J; Castelo, A; Capelozzi, V; Sette, A; Kitamura, S; Favero, M; Moreira-Filho, D C; Tavares, R; et al.
Abstract : Aims: To investigate the consequences of improvement in the workplace environment over six decades (1940–96) in asbestos miners and millers from a developing country (Brazil). Methods: A total of 3634 Brazilian workers with at least one year of exposure completed a respiratory symptoms questionnaire, chest radiography, and a spirometric evaluation. The study population was separated into three groups whose working conditions improved over time: group I (1940–66, n = 180), group II (1967–76, n = 1317), and group III (1977–96, n = 2137). Results: Respiratory symptoms were significantly related to spirometric abnormalities, smoking, and latency time. Breathlessness, in particular, was also associated with age, pleural abnormality and increased cumulative exposure to asbestos fibres. The odds ratios (OR) for parenchymal and/or non-malignant pleural disease were significantly lower in groups II and III compared to group I subjects (0.29 (0.12–0.69) and 0.19 (0.08–0.45), respectively), independent of age and smoking status. Similar results were found when groups were compared at equivalent latency times (groups I v II: 30–45 years; groups II v III: 20–25 years). Ageing, dyspnoea, past and current smoking, and radiographic abnormalities were associated with ventilatory impairment. Lower spirometric values were found in groups I and II compared to group III: lung function values were also lower in higher quartiles of latency and of cumulative exposure in these subjects. Conclusions: Progressive improvement in occupational hygiene in a developing country is likely to reduce the risk of non-malignant consequences of dust inhalation in asbestos miners and millers.